Od socrealistycznego pałacu po tonące w zieleni atria. Zarys historyczny poszukiwań architektury nowej siedziby Biblioteki Śląskiej w latach 1945–2000 (PDF 3,83 MB) (Książnica Śląska, 2025)
The article presents the results of research on architecture dedicatedto the new headquarters of the Silesian Library in Katowice. Efforts undertaken for over five decades in the second half of the 20th century to create a modern building for the Library resulted in a collectionof architectural designs developed by the most distinguished designers for the region, including Julian Duchowicz, Zygmunt Majerski,Tadeusz Łobos, Jurand Jarecki, Stanisław Kwaśniewicz and MarekGierlotka. The article complements and organizes knowledge aboutthese projects and conducts their synthetic stylistic analysis.